Sonographic Lower Uterine Segment Thickness After Prior Cesarean Section to Predict Uterine Rupture: A Systematic Review and Meta-analysis. Issue 2 (June 2020) - Swift, B.E.; Shah, P.S.; Farine, D.
Abstract : ( Anaesthesia . 2019;74:850–855) The rate of trial of labor after cesarean (TOLAC) in the United States has markedly dropped over the past few decades. Uterine rupture is the most serious complication associated with TOLAC, with the risk ranging from 0.52% for women in spontaneous labor to 2.45% for women undergoing labor induction with prostaglandin. This risk may be contributing to the declining rate of TOLAC. Sonographic measurement of the lower uterine segment thickness has been evaluated by several prospective studies, but the cutoff values for recommending TOLAC in these studies have differed due to varying ultrasound methodologies. This study analyzed the ultrasound methodology used in each study and then conducted a meta-analysis of the predictive value of sonographic measurement of the lower uterine segment thickness for uterine rupture during labor.